Effects of epidermal growth factor on transforming growth factor-beta1-induced epithelial-mesenchymal transition and potential mechanism in human corneal epithelial cells - Chen, Shu-Yang (Int J Ophthalmol, 2020)
AIM: To evaluate the effects of epidermal growth factor (EGF) on transforming growth factor-beta1 (TGF-β1)-induced epithelial-mesenchymal transition (EMT) in human corneal epithelial cells (HCECs). METHODS: HCECs were cultured and treated with TGF-β1 for establishing the model of EMT in vitro. Biological effect of EGF on TGF-β1-induced EMT was evaluated. Proteins and mRNAs expression changes of E-cadherin, N-cadherin and Fibronectin (EMT-relative markers) after TGF-β1 or TGF-β1 combined EGF treatment were detected by Western blot and RT-PCR, respectively. Viability and migration of HCECs were measured by CCK-8, transwell cell migration assay and cell scratch wound healing assay. Activation of Smad2, ERK, p38, JNK and Akt signaling pathways were evaluated by Western blot. Inhibitors of relevant signaling pathways were added to the HCECs to explore the key signal mechanism. RESULTS: With treatment of TGF-β1 only, three EMT-relative proteins and mRNA expression showed that EMT up-regulated in a concentration-dependent and time-dependent manner, with significantly decreasing cell viability (TGF-β1≥5 ng/mL, P<0.05) and increasing cell migration (TGF-β1≥5 ng/mL, P<0.01). The phosphorylation of Smad2 and p38 was a key process of TGF-β1-induced EMT. Meanwhile, EMT-relative proteins and mRNA expression showed that EGF inhibited TGF-β1-indued EMT, with significantly increasing cell viability (EGF≥10 ng/mL, P<0.01). It was noteworthy that EGF significantly enhanced cell migration although EMT was inhibited (EGF≥10 ng/mL, P<0.01), and the blockage of p38 (by SB202190, a p38 inhibitor) was a potential mechanism of this phenomenon. CONCLUSION: EGF inhibits TGF-β1-induced EMT via suppressive p38, and promotes cells proliferation and migration in a non-EMT process by inhibiting p38 pathway.